Preparation and characterization of Pd modified CeO2 nanoparticles for photocatalytic degradation of dye - Duangdao Channei (2018)
© 2018 Elsevier Masson SAS The aim of this work was to investigate the structural and optical properties of bare cerium dioxide (CeO2) and Pd-doped CeO2 (0.5, 1.0, 1.5 and 2.0 wt%) photocatalysts prepared by a combination of homogeneous precipitation and the impregnation method. X–ray diffraction analysis indicated that all samples were composed of the cubic fluorite phase of CeO2. Scanning electron micrographs revealed that all samples provided mostly spherical morphology with high agglomeration and estimated particle sizes ranging from 10 to 20 nm in diameter. The XPS core-level spectra of Pd species after incorporating 2.0 wt% Pd–doped CeO2 showed double peaks with binding energies of Pd3d5/2 and Pd3d3/2 corresponding to the Pd2+ oxidation state. The results from diffuse reflectance UV–visible spectroscopy showed that doping with Pd increased the absorbance onset of CeO2 to a longer wavelength, while the band gap decreased from 3.0 eV to 2.8 eV with 2.0% Pd doping concentration. This was likely due to the creation of impurity levels of Pd2+ inside the conduction and valence bands of CeO2. The photoluminescence spectra (PL) indicated that the emission peak intensity of CeO2 decreased in the presence of Pd2+ dopant in CeO2. This was associated with a decrease in the electron–hole recombination rate for electronically-excited. Photocatalytic activity for methyl orange dye degradation under visible light irradiation of 1.0 wt% Pd–doped CeO2 was determined as the optimal doping level with photocatalytic activity 5 times higher than that of bare CeO2 photocatalyst.